Hayatın Bı̇lgı̇sı̇ne ilı̇şkı̇n deneyı̇mler sunma boyutunda Hayat Bı̇lgı̇sı̇ ders kı̇taplarındakı̇ örnek olaylar ve işlevleri - (:unkn) unknown (My University, 2012)
Hayat Bilgisi ders kitapları, öğrencileri, yaşamla ilintili deneyimlerle karşılaştıracak, bu deneyimleri tartışmaları, sorgulamaları ve kişisel bir bakış geliştirmeleri noktasında önemlidir. Bu çerçevede Hayat Bilgisi ders kitaplarında kullanılan öğretim yöntemlerinden biri olan örnek olayın nicelik ve nitelik olarak nasıl kullanıldığı araştırmanın temel amaçlarından biridir. Bu amaçla 11 Hayat Bilgisi ders kitabı, doküman incelmesine tabi tutularak örnek olayın kullanılması boyutunda irdelenmiştir. Yine Hayat Bilgisi ders kitaplarını kullanan 65 öğretmenle de, ders kitaplarında yer alan örnek olaylara ilişkin bakış açılarını öğrenmek ve sınıfta nasıl kullandıklarıyla bağlantılı görüşlerini almak üzere görüşme yapılmıştır. Doküman incelemesi ve görüşmeden elde edilen veriler içerik analizine tabi tutularak analiz edilmiştir. Araştırma sonuçları örnek olayın Hayat Bilgisi ders kitaplarında en çok kullanılan öğretim yöntemi olduğunu; öğretmenlerin eski sistemin ders kitaplarıyla karşılaştırdıklarında gelişimi olumlu olarak değerlendirdiklerini göstermektedir.

Life studies textbooks help students to gain experience related to life itself, to discuss the issues and develop a personal stance on the life experiences. In this sense, the purpose of the present study is to illuminate in what ways the case study approach as one of the teaching methods used in the life studies textbooks can be used qualitative and quantitatively. The study designed based on the qualitative research orientation. Deskbased research and case study design was benefi ted in the study. Document analysis was the main approach adopted in desk-based research. A number of life studies textbooks (n=11) commonly used in elementary schools were selected and examined regarding the ways in which the case studies are used. Additionally, a range of elementary teachers (n=65) who use the books selected for the study were interviewed. Interviews aimed to explore the teachers’ views about the case studies as a teaching method and to fi nd out how they use case studies in their classes. Content analysis method was conducted for examining the data gathered from documents analysis and interviews. The fi ndings indicated that case studies were the most frequently used teaching method in the life studies textbooks. They also revealed that teachers’ preferences regarding case studies in the textbooks were in favor of the new life studies ones.
Case studies as a means of presenting daily life experiences and their functions in the life studies textbooks
Keywords: Eğitim, Eğitim Araştırmaları; Eğitim, Özel